A case report: enhanced somatostatin receptor expression in metastatic pancreatic neuroendocrine tumor following everolimus therapy - Zhang, Pei; Zhang, Chenyan; Xu, Huanji; Cao, Dan (Frontiers in Cell and Developmental Biology, 2025)
Pancreatic neuroendocrine tumors (pNETs) are rare and heterogeneous. Well-differentiated G1/G2 pNETs typically express somatostatin receptors (SSTRs), making them responsive to somatostatin analogue (SSA) therapy. However, therapeutic options become limited once SSTR expression decreases. This case report describes a 55-year-old man with grade 2 pNET who developed multiple liver metastases after undergoing pancreaticoduodenectomy in 2015. From August 2019 to October 2020, he received long-acting octreotide and transarterial chemoembolization (TACE), achieving stable disease. However, in August 2022, MRI scans indicated disease progression, leading to discontinuation of octreotide. In September 2022, oral surufatinib was initiated but paused in September 2023 due to adverse effects. In January 2024, everolimus therapy was started, resulting in a partial response by April 2024, with a significant reduction in liver metastases. Due to small intestinal ulcers, the dose of everolimus was reduced in August 2024. Follow-up scans showed stable disease through January 2025. In February 2025, [68Ga]Ga-DOTATATE PET/CT scans revealed significant re-expression of SSTR2 in liver lesions, likely induced by everolimus, allowing reinitiation of SSA therapy with increased octreotide dosage. This case demonstrates that everolimus can induce SSTR re-expression in advanced, SSTR-negative pNETs, offering new therapeutic possibilities. The “induction plus re-evaluation” approach could guide personalized treatment strategies in late-stage pNETs, although further studies are needed to validate this approach.